Crude glycerin in supplements for beef cattle at pasture during the dry season - Botini, Leonardo Antonio; Moraes, Kamila Andreatta Kling de; Moraes, Eduardo Henrique Bevitori Kling de; Pina, Douglas dos Santos; Paula, Diego Cordeiro de; Hoffmann, Alvair; Stinguel, Helio; Socreppa, Leandro Munhoz; Menezes, Daniel Mendonça de (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the effect of the replacement of corn by crude glycerin (CG) on the nutritional parameters and performance of beef cattle grazing Urochloa brizantha 'Marandu' during the dry season. To evaluate ruminal parameters, five non‑fistulated Nelore steers were used, with average initial body weight (BW) of 331.7±29.6 kg, allotted to a 5x5 Latin square. To evaluate performance, 30 steers were used, with average BW of 312.4±23.3 kg, allotted to a completely randomized design. Concentrated supplements (20% crude protein) with 0, 33, 66, and 100% CG replacing corn were evaluated and provided in the amount of 4.0 kg per animal per day. Intake of supplement, total, and pasture dry matter (DM), as well as of digestible organic matter (OM), presented quadratic behavior to the replacement levels. The apparent digestibility of DM, OM, neutral detergent fiber, and digestible OM, as well as average daily gain, also showed quadratic behavior. In concentrated supplements provided in the amount of 10 g kg‑1 body weight, the total replacement of corn by crude glycerin reduces supplement and digestible organic matter intake, besides the performance of grazing beef cattle.